'A Double Care': Prayer as Therapy in Early Modern England. (25th May 2019) - Mann, Sophie
Summary: This article explores three central questions. What did people consider the physical effects of prayer to be? Why were these effects considered to be therapeutic? How did an awareness of prayer's physiological benefits shape the practices of patients and practitioners? It also presents a wider attempt to incorporate the notion of 'double care' into our thinking about early modern medical treatment. To date, early modernists have demonstrated that the sick engaged in prayer in order to elicit the Lord's mercy and bring about a recovery. What remains underexplored is the way in which prayer was believed to somatically manifest in the devotee's own body. Exploring this theme will highlight that medical practitioners, clergymen and the laity perceived and invoked prayer as both a spiritual and physical aid. In this way, prayer was not only a central religious exercise but also could be an important component of early modern therapeutics.